Antioxidant and antibacterial effect of lemon verbena leaves’ (Lippia citriodora) extract as a natural preservative on refrigerated meat patties during storage - Younes Allam, Ayman; Farouk Elsadek, Mohamed; S. Al-Numair, Khalid; Abdelrasoul A. Badr, Adel; Singh, Sunita; Rafat Elkabary, Mohamed (Italian Journal of Food Science, 2024)
This study aims to determine the influence of adding lemon verbena leaf (LVL) extract on meat samples’ physicochemical, microbiological, and sensory properties. The ethanolic extracts (LVL-1, LVL-2, LVL-3, and LVL-4) revealed higher (p ≤ 0.05) content of phenolics and flavonoids than the aqueous extract (LVL-5). Then, LVL-1 extract was selected for antioxidant activity (DPPH) analysis (75.73%). LVLs’ ethanolic extracts at concentrations of 0.0%, 0.5%, and 1.0% were added to meat samples. Redness parameters and organoleptic properties were significantly affected. However, LVL-1.0% was more efficient in reducing microbial growth up to day 12 of the storage period; therefore, 0.5% LVL reduced discoloration and lipid oxidation without affecting organoleptic properties. Cooking yield and hardness were decreased effectively at a concentration of LVL-1.0%. LVL extract effectively delayed the lipid oxidation of meat samples. Redness parameters were affected, and this was also noted in sensory analysis. Adding 0.5% (LVL-0.5%) revealed high efficiency in retarding lipid oxidation and improving color stability in meat samples. In addition, no significant difference in sensory characteristics was identified between the experimental group and control treatments. Despite the beneficial effects on the fat peroxidation of meat patties, no level of LVL extract could delay microbiological degradation during storage at 4°C for 12 days. In this context, LVL extract is an alternate technique for producing meat and meat products with lower synthetic conservatives. Therefore, adding 0.5% LVL extract reduced discoloration and lipid oxidation without impacting sensory parameters, making it a viable option for processing meat samples. Finally, because no significant impacts (p ≥ 0.05) were found during the storage period when higher concentrations were utilized (LVL-1.0 %), the addition of LVLs (LVL-0.5%) is more recommended for application in meat and meat products.